Ответы и объяснения

2012-12-25T20:58:01+04:00

1. √2a - 2√18a + √72a = √2a - √4*18a + √72a = √2a - √72a + √72a = √2a

 

2. a) (4√3 - 2√5) * √3 + √60 = ( √16*3 - √4*5 ) * √3 + √60 = (√48 - √20) * √3 + √60 = √28 * √3 + √60 = √84 + √60 = √144 = 12

 

b) (√13 + 4)(4-√13) = 4√13 + 16 -13 - 4√13 = 16 - 13 = 3

 

c) (2√3 - 1)² + 2√12 = 12 - 4√3 + 1 + 2√12 = 13 - √16*3 + √4*12 = 13 - √48 + √48 = 13

 

3.

 х+√х       √х * √х + √х       √х(√х + 1)      √х + 1

-------- = ----------------- = -------------- = -----------

  х-1            √х * √х - 1       √х(√х - 1)       √х - 1